Physical education for combating obesity among Kuala Lumpur school students: a case study of SMK Taman Bukit Maluri, Kepong - Gunathevan Elumalai,; Sandakumary Munusamy,; Norkhalid Salimin,; Mohd. Izwan Shahril, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
For Asian population overweight has been defined as a body mass index (BMI) greater than 22.9kg/m2, with obesity defined as BMI greater than 25 kg/m2. The incidence of obesity has tripled in Malaysia since 1996, with one third of the adult population being currently overweight or obese. This study evaluated the effectiveness of an intervention programme on the level of Body Mass Index (BMI) of 40 purposely sampled form four overweight and obese female students from SMK Taman Bukit Maluri, Kepong, Kuala Lumpur. Data were obtained through the WHO (2004) BMI test procedure which was conducted before and after the 8-week intervention programme. Paired t-test analysis for the treatment group (N=20) indicated that the circuit training intervention programme was able to reduce the subjects BMI. In addition, the independent t-test for post test between both Treatment and control (N=20) groups also showed significant difference. Thus, it was proven that eight weeks of circuit training intervention programme was able to reduce the level of the students’ BMI even though the reduction level was not that high. If the programme was extended there would be greater changes in the students’ BMI levels and served as a good aid for Malaysia’s Physical Education teachers in their effort to combat student obesity.